2019
DOI: 10.3390/catal9040336
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Characteristics and Activities of Pd/γ-Al2O3 Catalysts Prepared by Vortex and Incipient Wetness Methods

Abstract: 5 wt% Pd/γ-Al2O3 catalysts were prepared by a modified Vortex Method (5-Pd-VM) and Incipient Wetness Method (5-Pd-IWM), and characterized by various techniques (Inductively coupled plasma atomic emission spectroscopy (ICP-AES), N2-physisorption, pulse CO chemisorption, temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS), scanning transmission electron microscopy (STEM), and X-ray diffraction (XRD)) under identical conditions. Both catalysts had similar particle sizes and dispersions;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…It has therefore found great applications in modern industry, such as catalytic exhaust converters aimed to reduce methane emission and catalytic gas turbine combustors designed to combust fuel under mild conditions [9,10]. Supported PdO catalysts have shown excellent catalytic property in methane oxidation, and currently are under extensive study [11][12][13][14][15][16][17][18]. However, once sulfur species (e.g., H 2 S or SO 2 ) are present in the reaction atmosphere, the poisoning of PdO catalyst which would lead to inactive PdO-SO x is irreversible and the activity of the catalyst cannot be recovered at relatively low temperature [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore found great applications in modern industry, such as catalytic exhaust converters aimed to reduce methane emission and catalytic gas turbine combustors designed to combust fuel under mild conditions [9,10]. Supported PdO catalysts have shown excellent catalytic property in methane oxidation, and currently are under extensive study [11][12][13][14][15][16][17][18]. However, once sulfur species (e.g., H 2 S or SO 2 ) are present in the reaction atmosphere, the poisoning of PdO catalyst which would lead to inactive PdO-SO x is irreversible and the activity of the catalyst cannot be recovered at relatively low temperature [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The negative peaks between 70 and 80 °C are due to the desorption of hydrogen adsorbed on the Pd metal surface during pretreatment or decomposition of palladium hydride (PdHx) formed by Pd chemisorption of H 2 . A broad peak was observed between 400 and 500 °C at 1% Pd@NDCS, which was attributed to PdO species that strongly interact with the carrier . In the catalysts 1%Co@NDCS and 1%Co-1%Pd@NDCS, the peaks between 450 and 500 °C were attributed to the reduction of Co 2+ to Co 0 .…”
Section: Resultsmentioning
confidence: 99%
“…47 A broad peak was observed between 400 and 500 °C at 1% Pd@NDCS, which was attributed to PdO species that strongly interact with the carrier. 48 In the catalysts 1%Co@ NDCS and 1%Co-1%Pd@NDCS, the peaks between 450 and 500 °C were attributed to the reduction of Co 2+ to Co 0 . 49 Compared to 1%Co@NDCS, the reduction peak of Co 2+ on 1%Co-1%Pd@NDCS shifted toward higher temperatures.…”
Section: Catalyst Characterizationmentioning
confidence: 93%
“…A PdO-PdO x /γAl 2 O 3 catalyst synthesized by a vortex-assisted incipient wetness method exhibited exceptional low-temperature activities, with 90-94% methane conversion at 300-320 • C. X-ray photoelectron spectroscopy established that the active phase, PdO x , originated from the interaction of PdO with the alumina support during the calcination process [14]. Banerjee et al [15] compared the relative efficiencies of Pd/alumina catalysts prepared by the vortex and incipient wetness methods. The catalyst synthesized by the vortex method produced smaller PdO/PdOx nanoparticles (2-5 nm) and converted 90% methane at 325 • C. Li et al [16] reported nitrogen-modified perovskite type composite catalysts prepared by a hydrothermal method for catalytic oxidation of methane.…”
Section: The Special Issuementioning
confidence: 99%